Управління фінансовими ресурсами об’єднаних територіальних громад в умовах адаптивних змін законодавства під час воєнного стану - Гордей, Оксана Дмитрівна; Рябокінь, Марина Валеріївна; Котух, Євген Володимирович; Новицька, Олена Валеріївна; Козій, Наталія Сергіївна; Оксана Гордей; Олена Новицька (Національний університет «Острозька академія», 2023)
Розглянуто основні умови функціонування об’єднаних територіальних громад у воєнний період. Вивчено сукупність нормативно-правових документів, які регулюють бюджетний процес ОТГ. Виявлено основні зміни, що відбулися під час розподілу фінансових ресурсів у 2022 р. Описано можливості ОТГ у перерозподілі фінансових ресурсів на пріоритетні для громад напрями під час війни. Виокремлено шляхи вдосконалення процесу управління фінансовими ресурсами ОТГ у воєнний період.

The decentralization reform created prerequisites for increasing the level of meeting the citizens’ needs and satisfying their interests. In the pre-war period, the process of decentralization ended with a clear division of functional powers between state and local budgets. Medium-term budget planning is decisive to ensure the program-target method of managing financial resources. The improvement of budget planning, execution, and reporting was ensured by the automation, in particular, the use of information and program complex “Local Budget” by united territorial communities (UTC). However, the war led to the emergence of financial risks for UTC. After the beginning of the aggressor country’s full-scale invasion, the redistribution of planned amounts of financial resources was necessary for the majority of Ukraine’s territory, therefore, in 2022, the regulatory and legal framework was improved to ensure that the financial needs of communities are met during wartime.
Keywords: фінансові ресурси; об’єднані територіальні громади; освітня субвенція; соціальні послуги; financial resources; united territorial communities; educational subvention; social services